Application of Identification to the Determination of Design Model Parameters of Bridge Structures - Dorobczyński, J.; Niczyj, J.; Paczkowski, W.M. (Engineering Transactions, 1991)
The paper presents the identification analysis of static and geometric characteristics of bridge structures. The least squares method was used for the comparison of strain gauge measurements and theoretical normal stresses values. The minimum of the objective function of the identification was defined by means of a controlled review of variations, Moreover, the values of variables of the calculation model corresponding to the real structure behaviour were set in the same way.